The role of Coenzyme Q10on the Total Antioxidant Capacity of Mouse Vitrified Pre-Antral Follicles - Hedayati Kashka, Roya; Zavareh, Saeed; Lashkarboluki, Taghi (Archives of Advances in Biosciences, 2015)
Occurrenceofoxidative stress (OS) following in vitro culture is inescapable. Therefore, the aim of the present study was to determine the efﬁcacy of Coenzyme Q10(CoQ10) supplementation medium on developments and Total Antioxidant Capacity (TAC) of mouse vitrified pre-antral follicles. Fresh and vitrified-warmed isolated preantral follicles from ovaries of 14-16 days-old mice were cultured in supplemented α- MEM medium with or without CoQ10.On the twelfth day of culture period,ovulation was induced by adding 1.5 IU/ml human Chorionic Gonadotropin (hCG). Rates of survival, antrum formation and developmental stages of released oocytes (GV, MI, MII) were evaluated. Separately,total antioxidant capacity (TAC) levels were measured at initial time, 24, 48, 72 and 96 hours of culture periodby ferric reducing/antioxidant power (FRAP) assay. The results showed that the mean diameter and rates of survival, antrum formation, ovulation and MII oocytes of fresh and vitrified-warmed isolated preantral follicles with pretreatment of CoQ10 were significantly higher than those of respective groups without pretreatment ofCoQ10. TAC levels significantly increased up to 96hours in fresh and vitrified-warmed preantral follicles with pre-treatment of CoQ10 compared with thosewhich were cultured without CoQ10. Supplemented culture medium with CoQ10 promotes TAC levels and development of both fresh and vitrified-warmed isolated preantral follicles.